Evaluation of elevated temperature oxidation of higher manganese ni-resist alloy - Khairul Ihsan, Yaakob; Mohd Rashidi, Maarof; Muhammad Aminuddin, Rosnizan (Akademi Baru, 2024)
Nowadays Nickel was used mostly in battery, elevated temperature application and also corrosive environment. The boost of electric and hybrid vehicle had maximized the usage of Nickel as main composition in alloying industry. As such the Nickel price was at peak and become volatile to interest manufacturer. Among affected compound is Ni-Resist alloy. In this study, an alloy known as ductile Ni-resist alloy was modifiedto minimize its processing cost by decreasing its Nickel weight percentage. The modification was investigated in order to reduce nickel usage in the alloying composition so the alloying process cost can be minimized. More than 12 wt% chromium and manganese werealloyed with 10 wt% nickel during melting stage. Then, the evaluation of properties, oxidation behavior and its microstructure were examined. The results indicated more carbide was formed which later decreased tensile strengthat elevated temperature. Oxidation resistanceincreased with addition of Mn/wt%. After oxidation at 765oC for 25 hours, there are oxide layers visible on the changed alloy.